2006
DOI: 10.1007/s11661-006-0141-8
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscope studies of Al-Fe-Si intermetallics in an Al-11 Pct Si alloy

Abstract: Al-Fe-Si intermetallic particlesinboth unmodified and highly modified sand-cast eutectic Al-11.7pct Si alloys were characterizedusing scanning and transmission electron microscopy,energy-dispersive X-ray spectroscopy,and convergent beam and selected area electron diffraction. The only twoAl-FeSi intermetallics observed in this particulara lloy are (1) ''Chinese-script''m orphology,c onsistent with ad escription of body-centered cubic a -Al 19 Fe 4 MnSi 2 and (2) plate-shaped, consistent with tetragonal d -Al 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 44 publications
(68 reference statements)
2
28
0
Order By: Relevance
“…The crystal structures are reported to be bodycentered-tetragonal (bct) for Al m Fe [5,12,18,19] and bodycentered-cubic (bcc) for a-Fe. [12,20,21] The difference in crystal structure results in the different EBSD patterns, and hence, the two iron-rich phases can easily be distinguished using EBSD. Therefore, it is evident that the Chinese script phase formed in the alloy of this study is Al m Fe rather than the a-Fe phase, which is observed in typical A206 Al-Cu casting alloys.…”
mentioning
confidence: 99%
“…The crystal structures are reported to be bodycentered-tetragonal (bct) for Al m Fe [5,12,18,19] and bodycentered-cubic (bcc) for a-Fe. [12,20,21] The difference in crystal structure results in the different EBSD patterns, and hence, the two iron-rich phases can easily be distinguished using EBSD. Therefore, it is evident that the Chinese script phase formed in the alloy of this study is Al m Fe rather than the a-Fe phase, which is observed in typical A206 Al-Cu casting alloys.…”
mentioning
confidence: 99%
“…However, when this ratio is low, around 2, only the a bcc -AlFeMnSi phase with Chinese script, star-like and polyhedral morphologies is formed, which has an increased sedimentation tendency [9] . For Al-Si alloys with a low Fe/Mn weight ratio of 1.2, the presence of cubic a and a bcc -AlFeMnSi phases, the latter described as Al 19 Fe 4 MnSi 2 , has been reported [5] . The formation of a hexagonal a h -AlFeMnSi phase, with a formula of Al 8 Fe 2 Si, has also been reported [6, 10 and 11] .…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the formation of different Iron-containing intermetallic phases [1][2][3][4] . Around 17 different intermetallic phases, with general composition of either aluminium-iron or Al-Fe-Si, have been summarized [5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 17 different intermetallic phases with a general composition of AleFe and AleFeeSi have been summarized in the literature in Ref. [5]. The ternary AleFeeSi system has been widely studied; experimental data pertaining to its intermetallic phases and their relationships in the corresponding phase diagram have been summarized in well-documented review papers in Ref.…”
Section: Introductionmentioning
confidence: 99%